2020
DOI: 10.3389/fimmu.2020.01043
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Basis of Immune Dysfunction Following Sepsis and Trauma

Abstract: Critically ill, severely injured and high-risk surgical patients are vulnerable to secondary infections during hospitalization and after hospital discharge. Studies show that the mitochondrial function and oxidative metabolism of monocytes and macrophages are impaired during sepsis. Alternatively, treatment with microbe-derived ligands, such as monophosphoryl lipid A (MPLA), peptidoglycan, or β-glucan, that interact with toll-like receptors and other pattern recognition receptors on leukocytes induces a state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 249 publications
(178 reference statements)
1
64
0
2
Order By: Relevance
“…This could lead to an altered immune response with a possible increased susceptibility to secondary infections. Again, the mitochondrial alterations are reminiscent of those observed in sepsis (Japiassu et al, 2011;Arulkumaran et al, 2016;Jang et al, 2019;McBride et al, 2020). Several studies in PBMC from patients with a systemic infection reported significant depolarization of mitochondrial membrane potential, reduced mitochondrial respiration, and severe impairment of mitochondrial electron transport chain complexes I, III, and IV (Japiassu et al, 2011;Jang et al, 2019;McBride et al, 2020).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…This could lead to an altered immune response with a possible increased susceptibility to secondary infections. Again, the mitochondrial alterations are reminiscent of those observed in sepsis (Japiassu et al, 2011;Arulkumaran et al, 2016;Jang et al, 2019;McBride et al, 2020). Several studies in PBMC from patients with a systemic infection reported significant depolarization of mitochondrial membrane potential, reduced mitochondrial respiration, and severe impairment of mitochondrial electron transport chain complexes I, III, and IV (Japiassu et al, 2011;Jang et al, 2019;McBride et al, 2020).…”
Section: Resultsmentioning
confidence: 90%
“…Again, the mitochondrial alterations are reminiscent of those observed in sepsis (Japiassu et al, 2011;Arulkumaran et al, 2016;Jang et al, 2019;McBride et al, 2020). Several studies in PBMC from patients with a systemic infection reported significant depolarization of mitochondrial membrane potential, reduced mitochondrial respiration, and severe impairment of mitochondrial electron transport chain complexes I, III, and IV (Japiassu et al, 2011;Jang et al, 2019;McBride et al, 2020). An association between mitochondrial dysfunctions and decreased ATP concentration in skeletal muscles has been correlated with organ failure, thus implying that bioenergetic failure can be a crucial pathological mechanism underlying multiorgan dysfunction (Brealey et al, 2002).…”
Section: Resultsmentioning
confidence: 98%
“…If immune scar observed in HF is similar to the one observed in sepsis, it could be interesting to consider these two common complications in elderly populations as unique models to propose strategies to restore immunity after prolonged stress-induced immune suppression. Most recently, the concept of metabolic dysfunction has emerged as a factor underlying impaired function of the innate and adaptive immune systems of severely injured patients (31).…”
Section: Discussionmentioning
confidence: 99%
“…As described in the previous section, cytokines are likely culprits in the central (i.e., hypothalamic and pituitary) suppression of the HPA, HPS and HPT axes in prolonged critical illness ( 29 ). Pro-inflammatory cytokines and inflammation also hinder normal mitochondrial function during critical illness ( 181 ). The alterations in cytokines found in critical illness likely have many further implications that have yet to be fully understood ( 182 ) which is also the case for ME/CFS ( 183 ).…”
Section: A “Vicious Circle” Perpetuating Illnessmentioning
confidence: 99%